Access to Maternal Healthcare Services during the Pandemic in Specialized Hospitals for Mother and Child - Abigael S. Pagatiku; Tentia Vitariani; Ibrahim Shihata; Bambang Ariyanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research aims to see how is access to maternal services in the pandemic era. Maternal patients with COVID-19 without symptoms (co-incidence) can only access a limited number of health facilities and make it more challenging to access healthcare services. Whereas previously, with the integrated referral system, it was easier for patients to access healthcare services. All childbirth during the pandemic takes place in a Healthcare Facility. Pregnant women with suspected, probable, and confirmed COVID-19 would have childbirth at a COVID-19 referral hospital. Based on our study results, as the conclusion, patients with an integrated referral system will be easy to get access to healthcare services. Maternal patients with confirmed COVID-19 without any symptoms have limited access to the health facilities, making access to healthcare services is not easy as before. Easy access to healthcare services is a patient’s right, including a pregnant women’s right with confirmed COVID-19. Therefore, the government needs to increase the number of COVID-19 Referral Hospital. To provide healthcare services, the Specialized Hospital for Mother and Child can handle the normal childbirth of COVID-19 patients. It is necessary to make regulations on the childbirth of COVID-19 patients at the Specialized Hospital for Mother and Child.